Hadith #446 - Sahih al-Bukhari - Hassan ibn Thabit (Sahih al-Bukhari)
I asked Abu Huraira “By Allah! Tell me the truth whether you heard the Prophet (ﷺ) saying, ‘O Hassan! Reply on behalf of Allah’s Messenger (ﷺ). O Allah! Help him with the Holy Spirit.” Abu Huraira said, “Yes . “
Grade: Sahih